The Genus Microchloa R.B.R. in India - Nair, K. K. N. (Indian Forester, 1980)
The genus Microchloa R. Br. Is reviewed and revised and a new key for separating the two species Microcholoa indica (Linn. F.) P. Beauv. And Microchloa kunthii Desv. is presented. A brief note on the ecology of the genus and the distribution of the two species in India is also given.